1989
DOI: 10.1152/ajprenal.1989.256.4.f664
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal diurnal rhythm of plasma vasopressin and urinary output in patients with enuresis

Abstract: The diurnal variation of plasma vasopressin (AVP), urinary excretion rate, urinary osmolality, and serum osmolality was studied twice in 15 patients with enuresis and in 11 age, weight, and sex matched nonenuretic normal subjects. A diurnal rhythm of AVP with constant levels during the day (8 AM-10 PM) and a highly significant increase during the night (10 PM-8 AM) was found in normal subjects. In contrast, enuretics showed a significantly less pronounced nocturnal increase in AVP with significantly lower noct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
231
1
18

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(257 citation statements)
references
References 0 publications
7
231
1
18
Order By: Relevance
“…Relative vasopressin deficiency during the night was demonstrated almost 20 years ago 11 and confirmed in a subset of MNE cases. 4,12 Nocturnal polyuria is present in about 2 of 3 enuretic patients, and it has been related to nocturnal vasopressin deficiency. 12,13 The MNE population has been divided into polyuric and nonpolyuric with the latter considered detrusor-dependent with small functional bladder capacity 1,6,14 or minor bladder dysfunction, which is common in daytime symptomatic enuretic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative vasopressin deficiency during the night was demonstrated almost 20 years ago 11 and confirmed in a subset of MNE cases. 4,12 Nocturnal polyuria is present in about 2 of 3 enuretic patients, and it has been related to nocturnal vasopressin deficiency. 12,13 The MNE population has been divided into polyuric and nonpolyuric with the latter considered detrusor-dependent with small functional bladder capacity 1,6,14 or minor bladder dysfunction, which is common in daytime symptomatic enuretic patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Nocturnal polyuria has been demonstrated frequently in MNE 3 and has been related to nocturnal vasopressin deficiency. 4 Desmopressin administration has been proposed and widely adopted for MNE treatment, 5 and enuretic patients have been differentiated into responders (65%) and nonresponders (35%). 6 Urinary electrolyte excretion has recently been studied in MNE.…”
mentioning
confidence: 99%
“…Following the observation by Rittig et al, that children with enuresis showed a significantly lower nocturnal increase in arginine-vasopressine (AVP) [3], it was subsequently used for an indication primarily seen in children; enuresis nocturna. Until now, DDAVP is the only drug therapy with evidence level 1, grade A recommendation, for the indication of monosymptomatic nocturnal enuresis (MNE) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a maturation rate of 15% per year, 0.5% of all cases remain in adulthood, with serious effects on self-esteem (6). Among various hypotheses on the pathophysiology of PNE, it has been proposed that patients with PNE have insufficient nightly increase of AVP, leading to the production of large amounts of dilute urine, thereby surpassing the bladder capacity (7). Successful application of a synthetic analogue of AVP, desmopressin (dDAVP), a V2R agonist, seemed to confirm this hypothesis.…”
mentioning
confidence: 99%